PENGARUH KREATIVITAS KARYAWAN TERHADAP PENGEMBANGAN INOVASI BARU BAGI PERUSAHAAN - Renny Aprilliyani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
As emmployees productivity can be affected by motivation, in order to improve the productivity, the company must give employees motivation, particularly motivation of reating good communication among employees, and creating new ideas, in wich such ideas will give the company strong influence in daily operational implementation. Again, with good work enviroment, there will be occupational innovations, so that it is possible to minimize occupational error as well as improve productivity.Creativiting can be arranged as a innovating strategy by a company in order to support its daily operations. In fact, based on the creative ideas, it is expected that there will be new innovations useful for company survival, particularly in global competition against other companies.